Traffic lane controller using RFID and IoT - Veera Boopathy E (Institute of Advanced Engineering and Science, 2020)
Traffic in urban areas is increasing day by day which leads to most critical issues of traffic management this paper proposes a smart and fully automatic traffic control system that will detect and control the congestion in real time, detect a stolen vehicle and also passes emergency vehicles smoothly with the use of passive RFID device. This effectively reduces travel delays and relieves congestion, it is necessary to control lane merge behaviours of freeway. Depending upon the count of vehicles green passage will be set dynamically and the proposed system provides special privileges for emergency vehicles like police vehicle, ambulance, VIP vehicles, etc.